2019
DOI: 10.1002/macp.201800515
|View full text |Cite
|
Sign up to set email alerts
|

Convective Patterns in Solution‐Casted Films from Acylated Hyaluronan

Abstract: The evaporation of thin solution layers is an important process taking place in fields such as distillation, coating, or thin film manufacturing. Under suitable conditions, evaporation can induce convective flow by creating gradients in surface tension (Bénard–Marangoni instability) or density. These phenomena have been studied by many authors, but detailed and illustrative visualizations of real experiments are surprisingly scarce compared to simulation results and drawn schemes. Therefore, detailed and repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Solutally induced Marangoni convection was investigated theoretically in various configurations [ 15 , 26 , 27 , 28 , 29 , 30 ]. Available experimental work on convective Marangoni instabilities in drying polymer films appear to be governed primarily by a deliberate use of Marangoni convection as means for self-assembly [ 18 , 31 , 32 , 33 ], including the transition between different modes of instability and lateral patterns of convection cells [ 17 , 18 , 34 , 35 , 36 , 37 , 38 , 39 ]. A quantitative assessment of the stability threshold of solutally induced Marangoni convection in drying polymer films based on experimental findings, as reported in [ 17 , 18 ], can be found but appears to be less frequent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Solutally induced Marangoni convection was investigated theoretically in various configurations [ 15 , 26 , 27 , 28 , 29 , 30 ]. Available experimental work on convective Marangoni instabilities in drying polymer films appear to be governed primarily by a deliberate use of Marangoni convection as means for self-assembly [ 18 , 31 , 32 , 33 ], including the transition between different modes of instability and lateral patterns of convection cells [ 17 , 18 , 34 , 35 , 36 , 37 , 38 , 39 ]. A quantitative assessment of the stability threshold of solutally induced Marangoni convection in drying polymer films based on experimental findings, as reported in [ 17 , 18 ], can be found but appears to be less frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors did not provide viscosity values, the dip-coating process implies a rather low initial viscosity [ 40 , 41 ]. Other authors reported less regular cells with different polygonal cells and large lateral size distributions having a standard deviation in the order of to [ 17 , 18 , 37 , 39 ]. In addition, it was found that the lateral cell size increased with increasing initial polymer concentration [ 32 , 39 ] and increasing initial film thickness [ 17 , 18 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing experimental work regarding convective instabilities in drying polymeric films appears to be governed primarily by deliberate patterning, utilizing Marangoni convection as a means for self-assembly [57][58][59][60]. The transition between different modes of instability and lateral size and form of convection cells was also investigated [58,59,[61][62][63][64][65][66][67]. When thermal and solutal gradients arise simultaneously, several authors conclude that the solutal effect is dominant [48,49,68].…”
Section: Marangoni Convection In Drying Polymer Filmsmentioning
confidence: 99%